Prevalence of Anxiety and Depression in Patient with Chronic Obstructive Pulmonary Disease - Sharma, Sita; Shakya, U.; Gorkhali, B.; Neupane, S. (Nepal Medical College Journal, 2018)
Anxiety and depression are very common comorbidities in patients with chronic obstructive pulmonary disease (COPD). This study was aimed at documenting the prevalence anxiety and depression in COPD patient attending tertiary level hospital. A quantitative cross sectional analytical study was carried out in 221 patients with previously diagnosed COPD. Participants were recruited from respiratory OPD at Tribhuvan University Teaching Hospital, Nepal. Anxiety and depression were screened using previously validated Nepalese version of Hospital Anxiety and Depression Scale (HADS) and dyspnea was assessed using the modified Medical Research Council Dyspnea Scale (mMRC). COPD Assessment Test (CAT) was used to measure the impact of COPD on daily life. Data was analyzed using SPSS version 16. Out of 221, 140 patients (63.3%) had anxiety and 153 patients (69.2%) had depression and 133 (60.2%) had both psychiatric symptoms. Factors associated with anxiety and depression in COPD patients were age, ethnicity, educational status, marital status, current working status, duration of illness, history of previous hospitalization, number of hospitalization in previous year, domiciliary oxygen therapy comorbidities along with dyspnea, CAT score. In conclusion, the study findings suggest that anxiety and depression are highly prevalent in COPD patients.